2012
DOI: 10.3382/ps.2011-01693
|View full text |Cite
|
Sign up to set email alerts
|

Effect of n-3 fatty acids on immune function in broiler chickens

Abstract: There is interest in the enrichment of poultry meat with long-chain n-3 polyunsaturated fatty acids in order to increase the consumption of these fatty acids by humans. However, there is concern that high levels of n-3 polyunsaturated fatty acids may have detrimental effects on immune function in chickens. The effect of feeding increasing levels of fish oil (FO) on immune function was investigated in broiler chickens. Three-week-old broilers were fed 1 of 4 wheat-soybean basal diets that contained 0, 30, 50, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 88 publications
5
50
0
Order By: Relevance
“…Another study revealed that inclusion of soybean oil in the diet could induce significant increases in serum corticosterone level. These results agree with studies that found that on weight of bursa Fabricius [29] , but it was not consistent with its effect on the weight of other organs (30). The results of this study indicated that the addition of that the addition of fish oil and soybean oil to the diet may be resulted in better improvement of immune response and performance in broiler chickens.…”
Section: Discussionsupporting
confidence: 82%
“…Another study revealed that inclusion of soybean oil in the diet could induce significant increases in serum corticosterone level. These results agree with studies that found that on weight of bursa Fabricius [29] , but it was not consistent with its effect on the weight of other organs (30). The results of this study indicated that the addition of that the addition of fish oil and soybean oil to the diet may be resulted in better improvement of immune response and performance in broiler chickens.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, income of fatty acids such as EPA and DHA by food is insufficient. An alternative source of the long-chain n-3 PUFA can be poultry meat if it could be enriched with appropriate fatty acids (Al-Khalifa et al 2012). The enrichment of broiler chicken meat with PUFA is a viable means of increasing PUFA consumption in European diets as intake of broiler chicken meat in the population is high (Rymer et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not clear whether this concern is justified, since some studies show no effect [15], some show a detrimental effect [16] while some show an improvement [16,17] in chicken immune response following feeding of n-3 PUFA.…”
Section: Involvement In Avian Immune Functionmentioning
confidence: 94%